K4 low-dielectric-loss cordierite microwave dielectric ceramic and preparation method thereof

CN123003273APending Publication Date: 2026-10-30HANGZHOU DIANZI UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311857106.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-29
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0006]鉴于以上所述现有材料的性能缺点,本发明的目的在于提供一种低介、低损耗堇青石型微波介质陶瓷材料的环结构调控正交实验方案、性能优化及制备方法、用途,用于解决现有技术中堇青石微波毫米波陶瓷材料品质因数低的问题

Benefits of technology

[0043]如上所述,本发明具有以下优点:对堇青石的内外元环同时进行调控,用Ni2+-Co2+掺杂外元环的Mg位,同时用四价离子和二价离子复合掺杂内元环的Al位,降低晶格振动,从而降低材料的本征损耗,获得低损耗堇青石型微波介电陶瓷。对结果进行极差分析,分析出影响微波介质性能的主次因素,并对实验因子和水平的搭配进行预测和验证。用少量的实验代替大量实验,并且使结果具有可信性和科学性。具体表现在Al位Mn4+-Zn2+复合离子掺杂的微波介质陶瓷材料的烧结温度为1300℃~1360℃、品质因数为24400GHz~86100GHz,谐振频率温度系数为-28.69~-19.10ppm/℃,介电常数为4.40~4.88。Al位Mn4+-Mg2+复合离子掺杂的微波介质陶瓷材料的烧结温度为1395℃~1420℃、品质因数为102900GHz~125700GHz,谐振频率温度系数为-25.94~-21.20ppm/℃,介电常数为4.56~4.77。Al位Ge4+-Zn2+复合离子掺杂的微波介质陶瓷材料的烧结温度为1340℃~1420℃、品质因数为31000GHz~119700GHz,谐振频率温度系数为-22.57~-17.67ppm/℃,介电常数为4.39~4.80。Al位Ge4+-Mg2+复合离子掺杂的微波介质陶瓷材料的烧结温度为1395℃~1420℃、品质因数为93500GHz~153400GHz,谐振频率温度系数为-25.52~-21.34ppm/℃,介电常数为4.51~4.71。该微波介质陶瓷材料的制备方法简单,具有较低的介电常数和较高的品质因数,有望成为毫米波应用的候选材料。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003273A_ABST
    Figure CN123003273A_ABST
Patent Text Reader

Abstract

The application provides a K4 low-dielectric-loss cordierite type microwave dielectric ceramic and a preparation method thereof. The chemical formula of the microwave dielectric ceramic is Mg 1.8 (N i1‑x Co x ) 0.2 Al 4‑y (A 0.5 B 0.5 ) y Si5O 18 , A = Mn, Ge, B = Zn, Mg, wherein 0.25 <= x <= 0.75, 0.10 <= y <= 0.25. The Mg site [Mg6O 2+ ] hexagonal outer ring is partially substituted by Ni 2+ -Co 36 composite ions, and the Al site [Al2Si4O 4+ ] hexagonal inner ring roundness is further partially substituted by A 2+ -B 18 composite ions, the product obtained by the application significantly reduces the dielectric loss of the ceramic material, the preparation process is simple, and the product has strong practicability as a functional dielectric ceramic material in 5G high-frequency bands and 6G millimeter wave communication.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of cordierite-type microwave dielectric ceramics, and in particular to a K4 low-dielectric-low-loss cordierite-type microwave dielectric ceramic and its preparation method. Background Technology

[0002] Miniaturized and highly integrated electronic components have become a key research focus for researchers worldwide. Microwave dielectric ceramics, as a new type of electronic ceramic material, are widely used in dielectric resonators, antennas, filters, substrates, and other applications due to their tunable dielectric constant, low dielectric loss, small temperature coefficient, and low cost.

[0003] With the rapid development of 5G communication technology, the operating frequency is required to be in the high-frequency microwave band (300MHz-300GHz). To meet the characteristics of low latency and high transmission rate of the transmitted signal, higher requirements are placed on the selection of dielectric materials. However, due to the late start of research in the field of electronic materials in China, many key materials are difficult to meet the needs of 5G communication equipment. Therefore, it is imperative to research and develop electronic materials with low dielectric constant and high quality factor.

[0004] Cordierite is a commonly used microwave dielectric ceramic with low dielectric constant, and its chemical formula is Mg2Al4Si5O. 18 The study focuses on cordierite with an orthorhombic crystal system and space group Cccm(66), which is mainly composed of Mg-O octahedra, Al-O tetrahedra, and Si-O tetrahedra. Among them, [Mg6O] lattice sites contain magnesium lattice sites. 36 [Al2Si4O] hexagonal outer ring and Al-Si lattice sites 18 The structure consists of two nested six-membered rings. The outer ring comprises six Mg-O octahedrons, four Al-O tetrahedrons, and two Si-O tetrahedrons; the inner ring contains two more six-membered rings composed of Si-O and Al-O tetrahedrons. Cordierite-type microwave dielectric ceramics have attracted extensive research due to their advantages such as low dielectric constant and temperature coefficient, and the ability to adjust microwave performance by controlling the symmetry of the six-membered rings. However, their high dielectric loss limits their practical application in the microwave and millimeter-wave fields.

[0005] The applicant has a long history of research on cordierite microwave ceramics, and in his early years he studied the [Mg6O] lattice sites of Mg. 36 Single-ion substitution of the hexagonal outer ring, and later doping of Mg sites by complex ions, such as Li + -Ga 3+ The research findings on replacing Mg were published in Ceramics International, Vol. 46, pp. 28631-28638 in 2020; using Ni 2+ -Co 2+Synergistic substitution occupies part of the Mg in the magnesia cordierite lattice 2+ The lattice positions have been determined, and a related patent was granted in 2023 (Chinese Patent CN115141006B); the influence of composite ions on Al-Si lattice sites [Al2Si4O] has also been recently studied. 18 Doping, using Mn 4+ -Zn 2+ Synergistic substitution occupies part of the Al in the magnesium cordierite lattice 3+ The lattice position was determined, and the research results were published in the Journal of European Ceramic Society, Vol. 42, pp. 5712-5717 in 2022. All of the above methods significantly improved the quality factor of cordierite to a certain extent. Summary of the Invention

[0006] In view of the performance shortcomings of the existing materials mentioned above, the purpose of this invention is to provide an orthogonal experimental scheme for ring structure control, performance optimization, preparation method and application of low dielectric and low loss cordierite microwave dielectric ceramic materials, in order to solve the problem of low quality factor of cordierite microwave and millimeter wave ceramic materials in the prior art.

[0007] To achieve the above objectives, the present invention is obtained through the following technical solution.

[0008] It should be noted that in the K4 low-dielectric-low-loss cordierite microwave dielectric ceramic described in this invention, K4 indicates that the dielectric constant is in the range of 4-5.

[0009] One of the objectives of this invention is to provide a K4 low-dielectric-low-loss cordierite-type microwave dielectric ceramic with the chemical formula Mg. 1.8 (Ni 1-x Co x ) 0.2 Al 4-y (A 0.5 B 0.5 ) y Si5O 18 Where the range of the subscript x is 0.25 ≤ x ≤ 0.75; the range of the subscript y is 0.10 ≤ y ≤ 0.25; A 0.5 B 0.5 Represents Mn 0.5 Zn 0.5 Mn 0.5 Mg 0.5 、Ge 0.5 Zn 0.5 、Ge 0.5 Mg 0.5 Any one of them;

[0010] Ni 2+ -Co2+ The substitution of some Mg in the magnesia cordierite lattice 2+ Lattice position;

[0011] Mn 4+ -Mg 2+ 、Ge 4+ -Mg 2+ Mn 4+ -Zn 2+ 、Ge 4+ -Zn 2+ Any group of composite ions in the magnesia cordierite lattice replaces a portion of the Al in the magnesia cordierite lattice. 3+ Lattice positions to achieve composite ion doping of Al 3+ ;

[0012] When Mn 4+ -Zn 2+ Composite ion-doped Al 3+ At that time, the quality factor of the low-dielectric-low-loss cordierite microwave dielectric ceramic is 24400GHz~86100GHz, the temperature coefficient of the resonant frequency is -28.70~-19.10ppm / ℃, and the dielectric constant is 4.40~4.90;

[0013] When Mn 4+ -Mg 2+ Composite ion-doped Al 3+ At that time, the quality factor of the low-dielectric-low-loss cordierite microwave dielectric ceramic is 102900GHz~125700GHz, the temperature coefficient of the resonant frequency is -25.90~-21.20ppm / ℃, and the dielectric constant is 4.60~4.80.

[0014] When Ge 4+ -Zn 2+ Composite ion-doped Al 3+ At that time, the quality factor of the low-dielectric-low-loss cordierite microwave dielectric ceramic is 31000GHz~119700GHz, the temperature coefficient of the resonant frequency is -22.57~-17.67ppm / ℃, and the dielectric constant is 4.39~4.80.

[0015] When Ge 4+ -Mg 2+ Composite ion-doped Al 3+ At that time, the quality factor of the low-dielectric-low-loss cordierite microwave dielectric ceramic is 935000GHz~153400GHz, the temperature coefficient of the resonant frequency is -25.50~-21.30ppm / ℃, and the dielectric constant is 4.50~4.70.

[0016] This invention also provides a method for preparing low-dielectric-low-loss cordierite-type microwave dielectric ceramics, comprising the following steps:

[0017] (1) Using MgO, NiO, CoO, Al2O3, MnO2, SiO2 and ZnO as raw materials, disperse them in the reaction medium according to the stoichiometric ratio of the chemical formula, grind them once, and dry them to obtain powder;

[0018] The chemical formula is: Mg 1.8 (Ni 1-x Co x ) 0.2 Al 4-y (Mn 0.5 Zn 0.5 ) y Si5O 18 Where the range of the subscript x is 0.25≤x≤0.75; and the range of the subscript y is 0.10≤y≤0.25;

[0019] (2) The powder is pre-calcined, then ground twice, dried, and granulated to obtain Ni-doped material. 2+ Co 2+ Mn 4+ Zn 2+ Ceramic raw materials;

[0020] The pre-firing process conditions are as follows: heating to 1200℃ at a heating rate of 3℃ / min and holding for 4 hours, and finally cooling down to 800℃ at a cooling rate of 3℃ / min and then naturally cooling.

[0021] (3) Sintering the doped Ni 2+ Co 2+ Mn 4+ Zn 2+ The microwave dielectric ceramic material is obtained from the ceramic raw materials.

[0022] The sintering process conditions are as follows: The ceramic green body is placed in a high-temperature furnace and heated to 800°C at a heating rate of 3°C / min, held at this temperature for 4 hours to remove the binder; after removing the binder, the temperature is increased to 1300°C–1360°C at a heating rate of 4°C / min and held for 4 hours, finally cooled to 800°C at a cooling rate of 3°C / min and allowed to cool naturally. Before sintering, the following steps are also included: Ni-doped... 2+ Co 2+ Mn 4+ Zn 2+ The ceramic raw materials are ground evenly, and a 10wt% polyvinyl alcohol solution is added. After mixing evenly, the mixture is passed through a 100-mesh nylon sieve. Each time, about 1 gram of powder is weighed and poured into a steel mold for pressing. The powder is pressed into a cylinder with a pressure of 1-5 MPa and held for 2 minutes.

[0023] This invention also provides a method for preparing low-dielectric-low-loss cordierite-type microwave dielectric ceramics, comprising the following steps:

[0024] (1) Using MgO, NiO, CoO, Al2O3, MnO2 and SiO2 as raw materials, disperse them in the reaction medium according to the stoichiometric ratio of the chemical formula, grind them once, and dry them to obtain powder;

[0025] The chemical formula is: Mg 1.8 (Ni 1-x Co x ) 0.2 Al 4-y (Mn 0.5 Mg 0.5 ) y Si5O 18 Where the range of the subscript x is 0.25≤x≤0.75; and the range of the subscript y is 0.10≤y≤0.25;

[0026] (2) The powder is pre-calcined, then ground twice, dried, and granulated to obtain Ni-doped material. 2+ Co 2+ Mn 4+ Mg 2+ The ceramic raw materials; the pre-firing process conditions are: heating to 1200℃ at a heating rate of 3℃ / min and holding for 4 hours, and finally cooling to 800℃ at a cooling rate of 3℃ / min and then naturally cooling.

[0027] (3) Sintering the doped Ni 2+ Co 2+ Mn 4+ Mg 2+ The microwave dielectric ceramic material is obtained from the ceramic raw materials.

[0028] The sintering process conditions are as follows: The ceramic green body is placed in a high-temperature furnace and heated to 800°C at a heating rate of 3°C / min, held at this temperature for 4 hours to remove the binder; after removing the binder, the temperature is increased to 1395°C–1420°C at a heating rate of 4°C / min and held for 4 hours, finally cooled to 800°C at a cooling rate of 3°C / min and allowed to cool naturally. Before sintering, the following steps are also included: Ni-doped... 2+ Co 2+ Mn 4+ Mg 2+ The ceramic raw materials are ground evenly, and a 10wt% polyvinyl alcohol solution is added. After mixing evenly, the mixture is passed through a 100-mesh nylon sieve. Each time, about 1 gram of powder is weighed and poured into a steel mold for pressing. The powder is pressed into a cylinder with a pressure of 1-5 MPa and held for 2 minutes.

[0029] This invention also provides a method for preparing K4 low-dielectric-low-loss cordierite-type microwave dielectric ceramics, comprising the following steps:

[0030] (1) Using MgO, NiO, CoO, Al2O3, GeO2, SiO2 and ZnO as raw materials, disperse them in the reaction medium according to the stoichiometric ratio of the chemical formula, grind them once, and dry them to obtain powder;

[0031] The chemical formula is: Mg 1.8 (Ni 1-x Co x ) 0.2 Al 4-y (Ge 0.5 Zn 0.5 ) y Si5O 18 Where the range of the subscript x is 0.25≤x≤0.75; and the range of the subscript y is 0.10≤y≤0.25;

[0032] (2) The powder is pre-calcined, then ground twice, dried, and granulated to obtain Ni-doped material. 2+ Co 2+ Ge 4+ Zn 2+ The ceramic raw materials; the pre-firing process conditions are: heating to 1200℃ at a heating rate of 3℃ / min and holding for 4 hours, and finally cooling to 800℃ at a cooling rate of 3℃ / min and then naturally cooling.

[0033] (3) Sintering the doped Ni 2+ Co 2+ Ge 4+ Zn 2+ The microwave dielectric ceramic material is obtained from the ceramic raw materials.

[0034] The sintering process conditions are as follows: The ceramic green body is placed in a high-temperature furnace and heated to 800°C at a heating rate of 3°C / min, held at this temperature for 4 hours to remove the binder; after removing the binder, the temperature is increased to 1340°C–1420°C at a heating rate of 4°C / min and held for 4 hours, finally cooled to 800°C at a cooling rate of 3°C / min and allowed to cool naturally. Before sintering, the following steps are also included: Ni-doped... 2+ Co 2+ Ge 4+ Zn 2+ The ceramic raw materials are ground evenly, and a 10wt% polyvinyl alcohol solution is added. After mixing evenly, the mixture is passed through a 100-mesh nylon sieve. Each time, about 1 gram of powder is weighed and poured into a steel mold for pressing. The powder is pressed into a cylinder with a pressure of 1-5 MPa and held for 2 minutes.

[0035] The present invention also provides a K4 low-dielectric-low-loss cordierite-type microwave dielectric ceramic, comprising the following steps:

[0036] (1) Using MgO, NiO, CoO, Al2O3, GeO2 and SiO2 as raw materials, disperse them in the reaction medium according to the stoichiometric ratio of the chemical formula, grind them once, and dry them to obtain powder;

[0037] The chemical formula is: Mg 1.8 (Ni 1-x Co x ) 0.2 Al 4-y (Ge 0.5 Mg 0.5 ) y Si5O 18 Where the range of the subscript x is 0.25≤x≤0.75; and the range of the subscript y is 0.10≤y≤0.25;

[0038] (2) The powder is pre-calcined, then ground twice, dried, and granulated to obtain Ni-doped material. 2+ Co 2+ Ge 4+ Mg 2+ The ceramic raw materials; the pre-firing process conditions are: heating to 1200℃ at a heating rate of 3℃ / min and holding for 4 hours, and finally cooling to 800℃ at a cooling rate of 3℃ / min and then naturally cooling.

[0039] (3) Sintering the doped Ni 2+ Co 2+ Ge 4+ Mg 2+ The microwave dielectric ceramic material is obtained from the ceramic raw materials.

[0040] The sintering process conditions are as follows: The ceramic green body is placed in a high-temperature furnace and heated to 800°C at a heating rate of 3°C / min, held at this temperature for 4 hours to remove the binder; after removing the binder, the temperature is increased to 1395°C–1420°C at a heating rate of 4°C / min and held for 4 hours, finally cooled to 800°C at a cooling rate of 3°C / min and allowed to cool naturally. Before sintering, the following steps are also included: Ni-doped... 2+ Co 2+ Ge 4+ Mg 2+ The ceramic raw materials are ground evenly, and a 10wt% polyvinyl alcohol solution is added. After mixing evenly, the mixture is passed through a 100-mesh nylon sieve. Each time, about 1 gram of powder is weighed and poured into a steel mold for pressing. The powder is pressed into a cylinder with a pressure of 1-5 MPa and held for 2 minutes.

[0041] Preferably, in step (1), the chemical formula is: Mg 1.8 (Ni 0.75 Co 0.25 ) 0.2 Al 3.85 (Ge0.5 Mg 0.5 ) 0.15 Si5O 18 ;

[0042] In step (3), the dielectric constant of the obtained microwave dielectric ceramic material is 4.59, the quality factor is 153386GHz, and the temperature coefficient of the resonant frequency is -25.518ppm / ℃.

[0043] As described above, the present invention has the following advantages: it simultaneously regulates the inner and outer rings of cordierite, using Ni 2+ -Co 2+ By doping the Mg sites of the outer rings and simultaneously doping the Al sites of the inner rings with a combination of tetravalent and divalent ions, lattice vibrations are reduced, thereby lowering the intrinsic loss of the material and obtaining low-loss cordierite-type microwave dielectric ceramics. Range analysis was performed on the results to identify the primary and secondary factors affecting the microwave dielectric performance, and the combination of experimental factors and levels was predicted and verified. A smaller number of experiments were used to replace a large number of experiments, ensuring the reliability and scientific validity of the results. Specifically, this is reflected in the Mn content at the Al sites. 4+ -Zn 2+ The sintering temperature of the composite ion-doped microwave dielectric ceramic material is 1300℃~1360℃, the quality factor is 24400GHz~86100GHz, the temperature coefficient of resonant frequency is -28.69~-19.10ppm / ℃, and the dielectric constant is 4.40~4.88. Al sites Mn 4+ -Mg 2+ The sintering temperature of the composite ion-doped microwave dielectric ceramic material is 1395℃~1420℃, the quality factor is 102900GHz~125700GHz, the temperature coefficient of resonant frequency is -25.94~-21.20ppm / ℃, and the dielectric constant is 4.56~4.77. Al-Ge 4 + -Zn 2+ The sintering temperature of the composite ion-doped microwave dielectric ceramic material is 1340℃~1420℃, the quality factor is 31000GHz~119700GHz, the temperature coefficient of resonant frequency is -22.57~-17.67ppm / ℃, and the dielectric constant is 4.39~4.80. Al-Ge 4+ -Mg 2+ The composite ion-doped microwave dielectric ceramic material has a sintering temperature of 1395℃~1420℃, a quality factor of 93500GHz~153400GHz, a resonant frequency temperature coefficient of -25.52~-21.34ppm / ℃, and a dielectric constant of 4.51~4.71. This microwave dielectric ceramic material has a simple preparation method, a low dielectric constant, and a high quality factor, making it a promising candidate material for millimeter-wave applications. Attached Figure Description

[0044] Figure 1 For Mg in Comparative Examples 1-3 and Examples 1-4 1.8 (Ni 1-x Co x ) 0.2 Al 4-y (Mn 0.5 Zn 0.5 ) y Si5O 18 The curves showing the change in microwave dielectric properties with Al site doping concentration y are shown.

[0045] Figure 2 For Mg in Comparative Examples 1-2 and Examples 5-8 1.8 (Ni 1-x Co x ) 0.2 Al 4-y (Mn 0.5 Mg 0.5 ) y Si5O 18 The curves showing the change in microwave dielectric properties with Al site doping concentration y are shown.

[0046] Figure 3 For Mg in Comparative Examples 1-2 and Examples 9-10 1.8 (Ni 1-x Co x ) 0.2 Al 4-y (Ge 0.5 Zn 0.5 ) y Si5O 18 The curves showing the change in microwave dielectric properties with Al site doping concentration y are shown.

[0047] Figure 4 For Mg in Comparative Examples 1-2 and Examples 12-16 1.8 (Ni 1-x Co x ) 0.2 Al 4-y (Ge 0.5 Mg 0.5 ) y Si5O 18 The curves showing the change in microwave dielectric properties with Al site doping concentration y are shown. Detailed Implementation

[0048] This invention designs an orthogonal experimental scheme, using Ni 2+ -Co 2+ While doping Mg sites with composite ions, Mn was used separately. 4 + -Zn2+ Mn 4+ -Mg 2+ 、Ge 4+ -Zn 2+ 、Ge 4+ -Mg 2+ Composite ion doping of Al sites; simultaneous modulation of [Mg6O] 36 ] and [Al2Si4O 18 The inner and outer rings of a six-membered ring are modified to improve microwave dielectric properties. The design steps of the scheme are as follows:

[0049] (1) Determine the composition of the composite ion at the Al-substituted site, the doping concentration, and the Ni at the Mg-substituted site. 2+ -Co 2+ The composite ion doping ratio was used to generate a three-factor, four-level orthogonal experimental table.

[0050] (2) The 16 groups were divided into four groups by dividing the four levels of the substitution factor at the Al position in the orthogonal experimental table into four equal groups, where 1 to 4 are Mn. 4+ -Zn 2+ 5-8 are Mn 4+ -Mg 2+ ,9~12 is Ge 4+ -Zn 2+ ,13~16 is Ge 4+ -Mg 2+ .

[0051] (3) Four levels of doping concentration were filled for each group, with 0.10, 0.15, 0.20 and 0.25 selected.

[0052] (4) Ni at the Mg site 2+ -Co 2+ The composite ion doping ratio is filled at four levels; that is, Ni 1-x Co x x takes values ​​of 0.25, 0.50, and 0.75. Since there are only three levels, four levels are needed to satisfy the orthogonal experimental table. At this time, the pseudo-level method is used to fill the fourth level with a better empirical value. Here, 0.50 is selected.

[0053] Table 1 Orthogonal Experiment Table

[0054]

[0055]

[0056] (5) Range analysis was performed on the quality factors of these 16 components, resulting in Table 2. R represents the range. The magnitude of the range allows analysis of the influence of each factor on the experimental index values, determining the primary and secondary relationships between factors, and thus identifying the optimal levels and combinations of the main factors. A larger range indicates a greater influence, and the degree of influence can be ranked as follows: Al-substituted components > Al-substituted concentration > Ni. 1-x Co x The value of x is taken from the table. That is, Al-position substitution is more advantageous than Mg-position substitution in improving the quality factor. In Table 2, K is the sum of the experimental index values ​​at each level, and k is the average of the experimental index values ​​at each level. Based on the value of k, the optimal combination scheme is selected: A4B2C3, i.e., Ge... 4+ -Mg 2+ Cooperative substitution of some Al sites, with a doping concentration of 0.15, Ni 1-x Co x The value of x was 0.75, and this group indeed had the highest quality factor in the experiment, indicating that the orthogonal experiment was scientific and feasible. It can be concluded that when Mg and Al sites are substituted simultaneously, the Al site doping concentration of 0.15 yields the best results.

[0057] Table 2 Range Analysis Table

[0058]

[0059]

[0060] Example 1

[0061] This embodiment provides a low dielectric constant, low loss microwave dielectric ceramic material Mg 1.8 (Ni 0.75 Co 0.25 ) 0.2 Al 3.9 (Mn 0.5 Zn 0.5 ) 0.1 Si5O 18 The preparation method includes the following steps:

[0062] (1) Weighing and batching: Weigh and batch the raw materials MgO, NiO, CoO, Al2O3, MnO2, ZnO and SiO2 that have undergone calcination and drying pretreatment according to the chemical formula stoichiometric ratio.

[0063] (2) First ball milling: Transfer the ingredients into the ball mill jar, add a certain amount of anhydrous ethanol as liquid medium and zirconium dioxide as grinding medium, seal the ball mill jar and place it in the ball mill for 12 hours. The speed is set to 220 r / min. After ball milling, put the slurry into the tray and transfer it into the oven to dry to constant weight.

[0064] (3) Pre-calcination: After drying, the powder is ground through a 100-mesh nylon sieve and then transferred into an alumina crucible. It is then placed in a high-temperature furnace and heated to 1200℃ at a heating rate of 3℃ / min and held for 4 hours.

[0065] (4) Secondary ball milling: Pour the pre-calcined raw material back into the ball mill jar, add a certain amount of anhydrous ethanol as a liquid medium, and put it into the ball mill for 12 hours. The speed is set to 220 r / min.

[0066] (5) Drying: Pour the slurry after the second ball milling into a tray and transfer it into an oven to dry until constant weight.

[0067] (6) Granulation: Grind the dried block raw material into powder, add binder (10wt% polyvinyl alcohol solution), mix evenly, pass through a 100-mesh nylon sieve, and select the powder that passes through as the raw material for the next step.

[0068] (7) Green body pressing: Weigh about 1 gram of powder and pour it into the mold. Then place it in the press and hold it under a pressure of 3 MPa for 2 minutes to press it into a ceramic green body with a diameter of 12 mm and a height of 5 mm.

[0069] (8) Sintering: The ceramic green body is placed in a high-temperature furnace and heated to 800℃ at a heating rate of 3℃ / min, held for 4 hours to remove the binder. After removing the binder, the temperature is increased to 1345℃ at a heating rate of 4℃ / min and held for 4 hours. Finally, the temperature is reduced to 800℃ at a cooling rate of 3℃ / min and allowed to cool naturally to obtain the microwave dielectric ceramic material Mg. 1.8 (Ni 0.75 Co 0.25 ) 0.2 Al 3.9 (Mn 0.5 Zn 0.5 ) 0.1 Si5O 18 ;

[0070] (9) Sample mechanical treatment and performance testing: The sintered microwave dielectric ceramic sample is ground and polished with a polishing machine, then ultrasonically cleaned, dried, and then its performance tested and packaged.

[0071] The microwave dielectric ceramic material prepared in this embodiment has a dielectric constant of 4.4, a quality factor of 49053 GHz, and a resonant frequency temperature coefficient of -23.41 ppm / ℃.

[0072] Example 2

[0073] This embodiment provides a low dielectric constant, low loss microwave dielectric ceramic material Mg 1.8 (Ni 0.5Co 0.5 ) 0.2 Al 3.85 (Mn 0.5 Zn 0.5 ) 0.15 Si5O 18 The preparation method includes the following steps:

[0074] (1) Weighing and batching: Weigh and batch the raw materials MgO, NiO, CoO, Al2O3, MnO2, ZnO and SiO2 that have undergone calcination and drying pretreatment according to the chemical formula stoichiometric ratio.

[0075] (2) First ball milling: Transfer the ingredients into the ball mill jar, add a certain amount of anhydrous ethanol as liquid medium and zirconium dioxide as grinding medium, seal the ball mill jar and place it in the ball mill for 12 hours. The speed is set to 220 r / min. After ball milling, put the slurry into the tray and transfer it into the oven to dry to constant weight.

[0076] (3) Pre-calcination: After drying, the powder is ground through a 100-mesh nylon sieve and then transferred into an alumina crucible. It is then placed in a high-temperature furnace and heated to 1200℃ at a heating rate of 3℃ / min and held for 4 hours.

[0077] (4) Secondary ball milling: Pour the pre-calcined raw material back into the ball mill jar, add a certain amount of anhydrous ethanol as a liquid medium, and put it into the ball mill for 12 hours. The speed is set to 220 r / min.

[0078] (5) Drying: Pour the slurry after the second ball milling into a tray and transfer it into an oven to dry until constant weight.

[0079] (6) Granulation: Grind the dried block raw material into powder, add binder (10wt% polyvinyl alcohol solution), mix evenly, pass through a 100-mesh nylon sieve, and select the powder that passes through as the raw material for the next step.

[0080] (7) Green body pressing: Weigh about 1 gram of powder and pour it into the mold. Then place it in the press and hold it under a pressure of 3 MPa for 2 minutes to press it into a ceramic green body with a diameter of 12 mm and a height of 5 mm.

[0081] (8) Sintering: The ceramic green body is placed in a high-temperature furnace and heated to 800℃ at a heating rate of 3℃ / min, held for 4 hours to remove the binder. After removing the binder, the temperature is increased to 1330℃ at a heating rate of 4℃ / min and held for 4 hours. Finally, the temperature is reduced to 800℃ at a cooling rate of 3℃ / min and allowed to cool naturally to obtain the microwave dielectric ceramic material Mg. 1.8 (Ni 0.5 Co 0.5 ) 0.2 Al3.85 (Mn 0.5 Zn 0.5 ) 0.15 Si5O 18 ;

[0082] (9) Sample mechanical treatment and performance testing: The sintered microwave dielectric ceramic sample is ground and polished with a polishing machine, then ultrasonically cleaned, dried, and then its performance tested and packaged.

[0083] The microwave dielectric ceramic material prepared in this embodiment has a dielectric constant of 4.67, a quality factor of 86058 GHz, and a resonant frequency temperature coefficient of -17.1 ppm / ℃.

[0084] Example 3

[0085] This embodiment provides a low dielectric constant, low loss microwave dielectric ceramic material Mg 1.8 (Ni 0.25 Co 0.75 ) 0.2 Al 3.8 (Mn 0.5 Zn 0.5 ) 0.2 Si5O 18 The preparation method includes the following steps:

[0086] (1) Weighing and batching: Weigh and batch the raw materials MgO, NiO, CoO, Al2O3, MnO2, ZnO and SiO2 that have undergone calcination and drying pretreatment according to the chemical formula stoichiometric ratio.

[0087] (2) First ball milling: Transfer the ingredients into the ball mill jar, add a certain amount of anhydrous ethanol as liquid medium and zirconium dioxide as grinding medium, seal the ball mill jar and place it in the ball mill for 12 hours. The speed is set to 220 r / min. After ball milling, put the slurry into the tray and transfer it into the oven to dry to constant weight.

[0088] (3) Pre-calcination: After drying, the powder is ground through a 100-mesh nylon sieve and then transferred into an alumina crucible. It is then placed in a high-temperature furnace and heated to 1200℃ at a heating rate of 3℃ / min and held for 4 hours.

[0089] (4) Secondary ball milling: Pour the pre-calcined raw material back into the ball mill jar, add a certain amount of anhydrous ethanol as a liquid medium, and put it into the ball mill for 12 hours. The speed is set to 220 r / min.

[0090] (5) Drying: Pour the slurry after the second ball milling into a tray and transfer it into an oven to dry until constant weight.

[0091] (6) Granulation: Grind the dried block raw material into powder, add binder (10wt% polyvinyl alcohol solution), mix evenly, pass through a 100-mesh nylon sieve, and select the powder that passes through as the raw material for the next step.

[0092] (7) Green body pressing: Weigh about 1 gram of powder and pour it into the mold. Then place it in the press and hold it under a pressure of 3 MPa for 2 minutes to press it into a ceramic green body with a diameter of 12 mm and a height of 5 mm.

[0093] (8) Sintering: The ceramic green body is placed in a high-temperature furnace and heated to 800℃ at a heating rate of 3℃ / min, held for 4 hours to remove the binder. After removing the binder, the temperature is increased to 1345℃ at a heating rate of 4℃ / min and held for 4 hours. Finally, the temperature is reduced to 800℃ at a cooling rate of 3℃ / min and allowed to cool naturally to obtain the microwave dielectric ceramic material Mg. 1.8 (Ni 0.5 Co 0.5 ) 0.2 Al 3.85 (Mn 0.5 Zn 0.5 ) 0.15 Si5O 18 ;

[0094] (9) Sample mechanical treatment and performance testing: The sintered microwave dielectric ceramic sample is ground and polished with a polishing machine, then ultrasonically cleaned, dried, and then its performance tested and packaged.

[0095] The microwave dielectric ceramic material prepared in this embodiment has a dielectric constant of 4.85, a quality factor of 24401 GHz, and a resonant frequency temperature coefficient of -24.96 ppm / ℃.

[0096] Example 4

[0097] This embodiment provides a low dielectric constant, low loss microwave dielectric ceramic material Mg 1.8 (Ni 0.5 Co 0.5 ) 0.2 Al 3.75 (Mn 0.5 Zn 0.5 ) 0.25 Si5O 18 The preparation method includes the following steps:

[0098] (1) Weighing and batching: Weigh and batch the raw materials MgO, NiO, CoO, Al2O3, MnO2, ZnO and SiO2 that have undergone calcination and drying pretreatment according to the chemical formula stoichiometric ratio.

[0099] (2) First ball milling: Transfer the ingredients into the ball mill jar, add a certain amount of anhydrous ethanol as liquid medium and zirconium dioxide as grinding medium, seal the ball mill jar and place it in the ball mill for 12 hours. The speed is set to 220 r / min. After ball milling, put the slurry into the tray and transfer it into the oven to dry to constant weight.

[0100] (3) Pre-calcination: After drying, the powder is ground through a 100-mesh nylon sieve and then transferred into an alumina crucible. It is then placed in a high-temperature furnace and heated to 1200℃ at a heating rate of 3℃ / min and held for 4 hours.

[0101] (4) Secondary ball milling: Pour the pre-calcined raw material back into the ball mill jar, add a certain amount of anhydrous ethanol as a liquid medium, and put it into the ball mill for 12 hours. The speed is set to 220 r / min.

[0102] (5) Drying: Pour the slurry after the second ball milling into a tray and transfer it into an oven to dry until constant weight.

[0103] (6) Granulation: Grind the dried block raw material into powder, add binder (10wt% polyvinyl alcohol solution), mix evenly, pass through a 100-mesh nylon sieve, and select the powder that passes through as the raw material for the next step.

[0104] (7) Green body pressing: Weigh about 1 gram of powder and pour it into the mold. Then place it in the press and hold it under a pressure of 3 MPa for 2 minutes to press it into a ceramic green body with a diameter of 12 mm and a height of 5 mm.

[0105] (8) Sintering: The ceramic green body is placed in a high-temperature furnace and heated to 800℃ at a heating rate of 3℃ / min, held for 4 hours to remove the binder. After removing the binder, the temperature is increased to 1300℃ at a heating rate of 4℃ / min and held for 4 hours. Finally, the temperature is reduced to 800℃ at a cooling rate of 3℃ / min and allowed to cool naturally to obtain the microwave dielectric ceramic material Mg. 1.8 (Ni 0.5 Co 0.5 ) 0.2 Al 3.75 (Mn 0.5 Zn 0.5 ) 0.25 Si5O 18 ;

[0106] (9) Sample mechanical treatment and performance testing: The sintered microwave dielectric ceramic sample is ground and polished with a polishing machine, then ultrasonically cleaned, dried, and then its performance tested and packaged.

[0107] The microwave dielectric ceramic material prepared in this embodiment has a dielectric constant of 4.88, a quality factor of 46482 GHz, and a resonant frequency temperature coefficient of -28.69 ppm / ℃.

[0108] Example 5

[0109] This embodiment provides a low dielectric constant, low loss microwave dielectric ceramic material Mg 1.8 (Ni 0.5 Co 0.5 ) 0.2 Al 3.9 (Mn 0.5 Mg 0.5 ) 0.1 Si5O 18 The preparation method includes the following steps:

[0110] (1) Weighing and batching: Weigh and batch the MgO, NiO, CoO, Al2O3, MnO2 and SiO2 raw materials that have undergone calcination and drying pretreatment according to the chemical formula stoichiometric ratio.

[0111] (2) First ball milling: Transfer the ingredients into the ball mill jar, add a certain amount of anhydrous ethanol as liquid medium and zirconium dioxide as grinding medium, seal the ball mill jar and place it in the ball mill for 12 hours. The speed is set to 220 r / min. After ball milling, put the slurry into the tray and transfer it into the oven to dry to constant weight.

[0112] (3) Pre-calcination: After drying, the powder is ground through a 100-mesh nylon sieve and then transferred into an alumina crucible. It is then placed in a high-temperature furnace and heated to 1200℃ at a heating rate of 3℃ / min and held for 4 hours.

[0113] (4) Secondary ball milling: Pour the pre-calcined raw material back into the ball mill jar, add a certain amount of anhydrous ethanol as a liquid medium, and put it into the ball mill for 12 hours. The speed is set to 220 r / min.

[0114] (5) Drying: Pour the slurry after the second ball milling into a tray and transfer it into an oven to dry until constant weight.

[0115] (6) Granulation: Grind the dried block raw material into powder, add binder (10wt% polyvinyl alcohol solution), mix evenly, pass through a 100-mesh nylon sieve, and select the powder that passes through as the raw material for the next step.

[0116] (7) Green body pressing: Weigh about 1 gram of powder and pour it into the mold. Then place it in the press and hold it under a pressure of 3 MPa for 2 minutes to press it into a ceramic green body with a diameter of 12 mm and a height of 5 mm.

[0117] (8) Sintering: The ceramic green body is placed in a high-temperature furnace and heated to 800℃ at a heating rate of 3℃ / min, held for 4 hours to remove the binder. After removing the binder, the temperature is increased to 1405℃ at a heating rate of 4℃ / min and held for 4 hours. Finally, the temperature is reduced to 800℃ at a cooling rate of 3℃ / min and allowed to cool naturally to obtain the microwave dielectric ceramic material Mg. 1.8 (Ni 0.5 Co 0.5 ) 0.2 Al 3.9 (Mn 0.5 Mg 0.5 ) 0.1 Si5O 18 ;

[0118] (9) Sample mechanical treatment and performance testing: The sintered microwave dielectric ceramic sample is ground and polished with a polishing machine, then ultrasonically cleaned, dried, and then its performance tested and packaged.

[0119] The microwave dielectric ceramic material prepared in this embodiment has a dielectric constant of 4.56, a quality factor of 114509 GHz, and a resonant frequency temperature coefficient of -22 ppm / ℃.

[0120] Example 6

[0121] This embodiment provides a low dielectric constant, low loss microwave dielectric ceramic material Mg 1.8 (Ni 0.75 Co 0.25 ) 0.2 Al 3.85 (Mn 0.5 Mg 0.5 ) 0.15 Si5O 18 The preparation method includes the following steps:

[0122] (1) Weighing and batching: Weigh and batch the MgO, NiO, CoO, Al2O3, MnO2 and SiO2 raw materials that have undergone calcination and drying pretreatment according to the chemical formula stoichiometric ratio.

[0123] (2) First ball milling: Transfer the ingredients into the ball mill jar, add a certain amount of anhydrous ethanol as liquid medium and zirconium dioxide as grinding medium, seal the ball mill jar and place it in the ball mill for 12 hours. The speed is set to 220 r / min. After ball milling, put the slurry into the tray and transfer it into the oven to dry to constant weight.

[0124] (3) Pre-calcination: After drying, the powder is ground through a 100-mesh nylon sieve and then transferred into an alumina crucible. It is then placed in a high-temperature furnace and heated to 1200℃ at a heating rate of 3℃ / min and held for 4 hours.

[0125] (4) Secondary ball milling: Pour the pre-calcined raw material back into the ball mill jar, add a certain amount of anhydrous ethanol as a liquid medium, and put it into the ball mill for 12 hours. The speed is set to 220 r / min.

[0126] (5) Drying: Pour the slurry after the second ball milling into a tray and transfer it into an oven to dry until constant weight.

[0127] (6) Granulation: Grind the dried block raw material into powder, add binder (10wt% polyvinyl alcohol solution), mix evenly, pass through a 100-mesh nylon sieve, and select the powder that passes through as the raw material for the next step.

[0128] (7) Green body pressing: Weigh about 1 gram of powder and pour it into the mold. Then place it in the press and hold it under a pressure of 3 MPa for 2 minutes to press it into a ceramic green body with a diameter of 12 mm and a height of 5 mm.

[0129] (8) Sintering: The ceramic green body is placed in a high-temperature furnace and heated to 800℃ at a heating rate of 3℃ / min, held for 4 hours to remove the binder. After removing the binder, the temperature is increased to 1405℃ at a heating rate of 4℃ / min and held for 4 hours. Finally, the temperature is reduced to 800℃ at a cooling rate of 3℃ / min and allowed to cool naturally to obtain the microwave dielectric ceramic material Mg. 1.8 (Ni 0.5 Co 0.5 ) 0.2 Al 3.9 (Mn 0.5 Mg 0.5 ) 0.1 Si5O 18 ;

[0130] (9) Sample mechanical treatment and performance testing: The sintered microwave dielectric ceramic sample is ground and polished with a polishing machine, then ultrasonically cleaned, dried, and then its performance tested and packaged.

[0131] The microwave dielectric ceramic material prepared in this embodiment has a dielectric constant of 4.65, a quality factor of 125691 GHz, and a resonant frequency temperature coefficient of -25.94 ppm / ℃.

[0132] Example 7

[0133] This embodiment provides a low dielectric constant, low loss microwave dielectric ceramic material Mg 1.8 (Ni 0.5 Co 0.5 ) 0.2 Al 3.8 (Mn 0.5 Mg 0.5 ) 0.2 Si5O18 The preparation method includes the following steps:

[0134] (1) Weighing and batching: Weigh and batch the MgO, NiO, CoO, Al2O3, MnO2 and SiO2 raw materials that have undergone calcination and drying pretreatment according to the chemical formula stoichiometric ratio.

[0135] (2) First ball milling: Transfer the ingredients into the ball mill jar, add a certain amount of anhydrous ethanol as liquid medium and zirconium dioxide as grinding medium, seal the ball mill jar and place it in the ball mill for 12 hours. The speed is set to 220 r / min. After ball milling, put the slurry into the tray and transfer it into the oven to dry to constant weight.

[0136] (3) Pre-calcination: After drying, the powder is ground through a 100-mesh nylon sieve and then transferred into an alumina crucible. It is then placed in a high-temperature furnace and heated to 1200℃ at a heating rate of 3℃ / min and held for 4 hours.

[0137] (4) Secondary ball milling: Pour the pre-calcined raw material back into the ball mill jar, add a certain amount of anhydrous ethanol as a liquid medium, and put it into the ball mill for 12 hours. The speed is set to 220 r / min.

[0138] (5) Drying: Pour the slurry after the second ball milling into a tray and transfer it into an oven to dry until constant weight.

[0139] (6) Granulation: Grind the dried block raw material into powder, add binder (10wt% polyvinyl alcohol solution), mix evenly, pass through a 100-mesh nylon sieve, and select the powder that passes through as the raw material for the next step.

[0140] (7) Green body pressing: Weigh about 1 gram of powder and pour it into the mold. Then place it in the press and hold it under a pressure of 3 MPa for 2 minutes to press it into a ceramic green body with a diameter of 12 mm and a height of 5 mm.

[0141] (8) Sintering: The ceramic green body is placed in a high-temperature furnace and heated to 800℃ at a heating rate of 3℃ / min, held for 4 hours to remove the binder. After removing the binder, the temperature is increased to 1415℃ at a heating rate of 4℃ / min and held for 4 hours. Finally, the temperature is reduced to 800℃ at a cooling rate of 3℃ / min and allowed to cool naturally to obtain the microwave dielectric ceramic material Mg. 1.8 (Ni 0.5 Co 0.5 ) 0.2 Al 3.8 (Mn 0.5 Mg 0.5 ) 0.2 Si5O 18 ;

[0142] (9) Sample mechanical treatment and performance testing: The sintered microwave dielectric ceramic sample is ground and polished with a polishing machine, then ultrasonically cleaned, dried, and then its performance tested and packaged.

[0143] The microwave dielectric ceramic material prepared in this embodiment has a dielectric constant of 4.73, a quality factor of 106395 GHz, and a resonant frequency temperature coefficient of -24.48 ppm / ℃.

[0144] Example 8

[0145] This embodiment provides a low dielectric constant, low loss microwave dielectric ceramic material Mg 1.8 (Ni 0.25 Co 0.75 ) 0.2 Al 3.75 (Mn 0.5 Mg 0.5 ) 0.25 Si5O 18 The preparation method includes the following steps:

[0146] (1) Weighing and batching: Weigh and batch the MgO, NiO, CoO, Al2O3, MnO2 and SiO2 raw materials that have undergone calcination and drying pretreatment according to the chemical formula stoichiometric ratio.

[0147] (2) First ball milling: Transfer the ingredients into the ball mill jar, add a certain amount of anhydrous ethanol as liquid medium and zirconium dioxide as grinding medium, seal the ball mill jar and place it in the ball mill for 12 hours. The speed is set to 220 r / min. After ball milling, put the slurry into the tray and transfer it into the oven to dry to constant weight.

[0148] (3) Pre-calcination: After drying, the powder is ground through a 100-mesh nylon sieve and then transferred into an alumina crucible. It is then placed in a high-temperature furnace and heated to 1200℃ at a heating rate of 3℃ / min and held for 4 hours.

[0149] (4) Secondary ball milling: Pour the pre-calcined raw material back into the ball mill jar, add a certain amount of anhydrous ethanol as a liquid medium, and put it into the ball mill for 12 hours. The speed is set to 220 r / min.

[0150] (5) Drying: Pour the slurry after the second ball milling into a tray and transfer it into an oven to dry until constant weight.

[0151] (6) Granulation: Grind the dried block raw material into powder, add binder (10wt% polyvinyl alcohol solution), mix evenly, pass through a 100-mesh nylon sieve, and select the powder that passes through as the raw material for the next step.

[0152] (7) Green body pressing: Weigh about 1 gram of powder and pour it into the mold. Then place it in the press and hold it under a pressure of 3 MPa for 2 minutes to press it into a ceramic green body with a diameter of 12 mm and a height of 5 mm.

[0153] (8) Sintering: The ceramic green body is placed in a high-temperature furnace and heated to 800℃ at a heating rate of 3℃ / min, held for 4 hours to remove the binder. After removing the binder, the temperature is increased to 1410℃ at a heating rate of 4℃ / min and held for 4 hours. Finally, the temperature is reduced to 800℃ at a cooling rate of 3℃ / min and allowed to cool naturally to obtain the microwave dielectric ceramic material Mg. 1.8 (Ni 0.25 Co 0.75 ) 0.2 Al 3.75 (Mn 0.5 Mg 0.5 ) 0.25 Si5O 18 ;

[0154] (9) Sample mechanical treatment and performance testing: The sintered microwave dielectric ceramic sample is ground and polished with a polishing machine, then ultrasonically cleaned, dried, and then its performance tested and packaged.

[0155] The microwave dielectric ceramic material prepared in this embodiment has a dielectric constant of 4.77, a quality factor of 102891 GHz, and a resonant frequency temperature coefficient of -21.2 ppm / ℃.

[0156] Example 9

[0157] This embodiment provides a low dielectric constant, low loss microwave dielectric ceramic material Mg 1.8 (Ni 0.25 Co 0.75 ) 0.2 Al 3.9 (Ge 0.5 Zn 0.5 ) 0.1 Si5O 18 The preparation method includes the following steps:

[0158] (1) Weighing and batching: Weigh and batch the MgO, NiO, CoO, Al2O3, GeO2, ZnO and SiO2 raw materials that have undergone calcination and drying pretreatment according to the chemical formula stoichiometric ratio.

[0159] (2) First ball milling: Transfer the ingredients into the ball mill jar, add a certain amount of anhydrous ethanol as liquid medium and zirconium dioxide as grinding medium, seal the ball mill jar and place it in the ball mill for 12 hours. The speed is set to 220 r / min. After ball milling, put the slurry into the tray and transfer it into the oven to dry to constant weight.

[0160] (3) Pre-calcination: After drying, the powder is ground through a 100-mesh nylon sieve and then transferred into an alumina crucible. It is then placed in a high-temperature furnace and heated to 1200℃ at a heating rate of 3℃ / min and held for 4 hours.

[0161] (4) Secondary ball milling: Pour the pre-calcined raw material back into the ball mill jar, add a certain amount of anhydrous ethanol as a liquid medium, and put it into the ball mill for 12 hours. The speed is set to 220 r / min.

[0162] (5) Drying: Pour the slurry after the second ball milling into a tray and transfer it into an oven to dry until constant weight.

[0163] (6) Granulation: Grind the dried block raw material into powder, add binder (10wt% polyvinyl alcohol solution), mix evenly, pass through a 100-mesh nylon sieve, and select the powder that passes through as the raw material for the next step.

[0164] (7) Green body pressing: Weigh about 1 gram of powder and pour it into the mold. Then place it in the press and hold it under a pressure of 3 MPa for 2 minutes to press it into a ceramic green body with a diameter of 12 mm and a height of 5 mm.

[0165] (8) Sintering: The ceramic green body is placed in a high-temperature furnace and heated to 800℃ at a heating rate of 3℃ / min, held for 4 hours to remove the binder. After removing the binder, the temperature is increased to 1375℃ at a heating rate of 4℃ / min and held for 4 hours. Finally, the temperature is reduced to 800℃ at a cooling rate of 3℃ / min and allowed to cool naturally to obtain the microwave dielectric ceramic material Mg. 1.8 (Ni 0.25 Co 0.75 ) 0.2 Al 3.9 (Ge 0.5 Zn 0.5 ) 0.1 Si5O 18 ;

[0166] (9) Sample mechanical treatment and performance testing: The sintered microwave dielectric ceramic sample is ground and polished with a polishing machine, then ultrasonically cleaned, dried, and then its performance tested and packaged.

[0167] The microwave dielectric ceramic material prepared in this embodiment has a dielectric constant of 4.39, a quality factor of 109458 GHz, and a resonant frequency temperature coefficient of -22.25 ppm / ℃.

[0168] Example 10

[0169] This embodiment provides a low dielectric constant, low loss microwave dielectric ceramic material Mg 1.8 (Ni0.5 Co 0.5 ) 0.2 Al 3.85 (Ge 0.5 Zn 0.5 ) 0.15 Si5O 18 The preparation method includes the following steps:

[0170] (1) Weighing and batching: Weigh and batch the MgO, NiO, CoO, Al2O3, GeO2, ZnO and SiO2 raw materials that have undergone calcination and drying pretreatment according to the chemical formula stoichiometric ratio.

[0171] (2) First ball milling: Transfer the ingredients into the ball mill jar, add a certain amount of anhydrous ethanol as liquid medium and zirconium dioxide as grinding medium, seal the ball mill jar and place it in the ball mill for 12 hours. The speed is set to 220 r / min. After ball milling, put the slurry into the tray and transfer it into the oven to dry to constant weight.

[0172] (3) Pre-calcination: After drying, the powder is ground through a 100-mesh nylon sieve and then transferred into an alumina crucible. It is then placed in a high-temperature furnace and heated to 1200℃ at a heating rate of 3℃ / min and held for 4 hours.

[0173] (4) Secondary ball milling: Pour the pre-calcined raw material back into the ball mill jar, add a certain amount of anhydrous ethanol as a liquid medium, and put it into the ball mill for 12 hours. The speed is set to 220 r / min.

[0174] (5) Drying: Pour the slurry after the second ball milling into a tray and transfer it into an oven to dry until constant weight.

[0175] (6) Granulation: Grind the dried block raw material into powder, add binder (10wt% polyvinyl alcohol solution), mix evenly, pass through a 100-mesh nylon sieve, and select the powder that passes through as the raw material for the next step.

[0176] (7) Green body pressing: Weigh about 1 gram of powder and pour it into the mold. Then place it in the press and hold it under a pressure of 3 MPa for 2 minutes to press it into a ceramic green body with a diameter of 12 mm and a height of 5 mm.

[0177] (8) Sintering: The ceramic green body is placed in a high-temperature furnace and heated to 800℃ at a heating rate of 3℃ / min, held for 4 hours to remove the binder. After removing the binder, the temperature is increased to 1400℃ at a heating rate of 4℃ / min and held for 4 hours. Finally, the temperature is reduced to 800℃ at a cooling rate of 3℃ / min and allowed to cool naturally to obtain the microwave dielectric ceramic material Mg. 1.8 (Ni 0.5 Co 0.5 ) 0.2 Al3.85 (Ge 0.5 Zn 0.5 ) 0.15 Si5O 18 ;

[0178] (9) Sample mechanical treatment and performance testing: The sintered microwave dielectric ceramic sample is ground and polished with a polishing machine, then ultrasonically cleaned, dried, and then its performance tested and packaged.

[0179] The microwave dielectric ceramic material prepared in this embodiment has a dielectric constant of 4.75, a quality factor of 119721 GHz, and a resonant frequency temperature coefficient of -22.57 ppm / ℃.

[0180] Example 11

[0181] This embodiment provides a low dielectric constant, low loss microwave dielectric ceramic material Mg 1.8 (Ni 0.75 Co 0.25 ) 0.2 Al 3.8 (Ge 0.5 Zn 0.5 ) 0.2 Si5O 18 The preparation method includes the following steps:

[0182] (1) Weighing and batching: Weigh and batch the MgO, NiO, CoO, Al2O3, GeO2, ZnO and SiO2 raw materials that have undergone calcination and drying pretreatment according to the chemical formula stoichiometric ratio.

[0183] (2) First ball milling: Transfer the ingredients into the ball mill jar, add a certain amount of anhydrous ethanol as liquid medium and zirconium dioxide as grinding medium, seal the ball mill jar and place it in the ball mill for 12 hours. The speed is set to 220 r / min. After ball milling, put the slurry into the tray and transfer it into the oven to dry to constant weight.

[0184] (3) Pre-calcination: After drying, the powder is ground through a 100-mesh nylon sieve and then transferred into an alumina crucible. It is then placed in a high-temperature furnace and heated to 1200℃ at a heating rate of 3℃ / min and held for 4 hours.

[0185] (4) Secondary ball milling: Pour the pre-calcined raw material back into the ball mill jar, add a certain amount of anhydrous ethanol as a liquid medium, and put it into the ball mill for 12 hours. The speed is set to 220 r / min.

[0186] (5) Drying: Pour the slurry after the second ball milling into a tray and transfer it into an oven to dry until constant weight.

[0187] (6) Granulation: Grind the dried block raw material into powder, add binder (10wt% polyvinyl alcohol solution), mix evenly, pass through a 100-mesh nylon sieve, and select the powder that passes through as the raw material for the next step.

[0188] (7) Green body pressing: Weigh about 1 gram of powder and pour it into the mold. Then place it in the press and hold it under a pressure of 3 MPa for 2 minutes to press it into a ceramic green body with a diameter of 12 mm and a height of 5 mm.

[0189] (8) Sintering: The ceramic green body is placed in a high-temperature furnace and heated to 800℃ at a heating rate of 3℃ / min, held for 4 hours to remove the binder. After removing the binder, the temperature is increased to 1340℃ at a heating rate of 4℃ / min and held for 4 hours. Finally, the temperature is reduced to 800℃ at a cooling rate of 3℃ / min and allowed to cool naturally to obtain the microwave dielectric ceramic material Mg. 1.8 (Ni 0.75 Co 0.25 ) 0.2 Al 3.8 (Ge 0.5 Zn 0.5 ) 0.2 Si5O 18 ;

[0190] (9) Sample mechanical treatment and performance testing: The sintered microwave dielectric ceramic sample is ground and polished with a polishing machine, then ultrasonically cleaned, dried, and then its performance tested and packaged.

[0191] The microwave dielectric ceramic material prepared in this embodiment has a dielectric constant of 4.63, a quality factor of 83055 GHz, and a resonant frequency temperature coefficient of -21.33 ppm / ℃.

[0192] Example 12

[0193] This embodiment provides a low dielectric constant, low loss microwave dielectric ceramic material Mg 1.8 (Ni 0.5 Co 0.5 ) 0.2 Al 3.75 (Ge 0.5 Zn 0.5 ) 0.25 Si5O 18 The preparation method includes the following steps:

[0194] (1) Weighing and batching: Weigh and batch the MgO, NiO, CoO, Al2O3, GeO2, ZnO and SiO2 raw materials that have undergone calcination and drying pretreatment according to the chemical formula stoichiometric ratio.

[0195] (2) First ball milling: Transfer the ingredients into the ball mill jar, add a certain amount of anhydrous ethanol as liquid medium and zirconium dioxide as grinding medium, seal the ball mill jar and place it in the ball mill for 12 hours. The speed is set to 220 r / min. After ball milling, put the slurry into the tray and transfer it into the oven to dry to constant weight.

[0196] (3) Pre-calcination: After drying, the powder is ground through a 100-mesh nylon sieve and then transferred into an alumina crucible. It is then placed in a high-temperature furnace and heated to 1200℃ at a heating rate of 3℃ / min and held for 4 hours.

[0197] (4) Secondary ball milling: Pour the pre-calcined raw material back into the ball mill jar, add a certain amount of anhydrous ethanol as a liquid medium, and put it into the ball mill for 12 hours. The speed is set to 220 r / min.

[0198] (5) Drying: Pour the slurry after the second ball milling into a tray and transfer it into an oven to dry until constant weight.

[0199] (6) Granulation: Grind the dried block raw material into powder, add binder (10wt% polyvinyl alcohol solution), mix evenly, pass through a 100-mesh nylon sieve, and select the powder that passes through as the raw material for the next step.

[0200] (7) Green body pressing: Weigh about 1 gram of powder and pour it into the mold. Then place it in the press and hold it under a pressure of 3 MPa for 2 minutes to press it into a ceramic green body with a diameter of 12 mm and a height of 5 mm.

[0201] (8) Sintering: The ceramic green body is placed in a high-temperature furnace and heated to 800℃ at a heating rate of 3℃ / min, held for 4 hours to remove the binder. After removing the binder, the temperature is increased to 1410℃ at a heating rate of 4℃ / min and held for 4 hours. Finally, the temperature is reduced to 800℃ at a cooling rate of 3℃ / min and allowed to cool naturally to obtain the microwave dielectric ceramic material Mg. 1.8 (Ni 0.5 Co 0.5 ) 0.2 Al 3.75 (Ge 0.5 Zn 0.5 ) 0.25 Si5O 18 ;

[0202] (9) Sample mechanical treatment and performance testing: The sintered microwave dielectric ceramic sample is ground and polished with a polishing machine, then ultrasonically cleaned, dried, and then its performance tested and packaged.

[0203] The microwave dielectric ceramic material prepared in this embodiment has a dielectric constant of 4.8, a quality factor of 30981 GHz, and a resonant frequency temperature coefficient of -17.67 ppm / ℃.

[0204] Example 13

[0205] This embodiment provides a low dielectric constant, low loss microwave dielectric ceramic material Mg 1.8 (Ni 0.5 Co 0.5 ) 0.2 Al 3.9 (Ge 0.5 Mg 0.5 ) 0.1 Si5O 18 The preparation method includes the following steps:

[0206] (1) Weighing and batching: Weigh and batch the MgO, NiO, CoO, Al2O3, GeO2 and SiO2 raw materials that have undergone calcination and drying pretreatment according to the chemical formula stoichiometric ratio.

[0207] (2) First ball milling: Transfer the ingredients into the ball mill jar, add a certain amount of anhydrous ethanol as liquid medium and zirconium dioxide as grinding medium, seal the ball mill jar and place it in the ball mill for 12 hours. The speed is set to 220 r / min. After ball milling, put the slurry into the tray and transfer it into the oven to dry to constant weight.

[0208] (3) Pre-calcination: After drying, the powder is ground through a 100-mesh nylon sieve and then transferred into an alumina crucible. It is then placed in a high-temperature furnace and heated to 1200℃ at a heating rate of 3℃ / min and held for 4 hours.

[0209] (4) Secondary ball milling: Pour the pre-calcined raw material back into the ball mill jar, add a certain amount of anhydrous ethanol as a liquid medium, and put it into the ball mill for 12 hours. The speed is set to 220 r / min.

[0210] (5) Drying: Pour the slurry after the second ball milling into a tray and transfer it into an oven to dry until constant weight.

[0211] (6) Granulation: Grind the dried block raw material into powder, add binder (10wt% polyvinyl alcohol solution), mix evenly, pass through a 100-mesh nylon sieve, and select the powder that passes through as the raw material for the next step.

[0212] (7) Green body pressing: Weigh about 1 gram of powder and pour it into the mold. Then place it in the press and hold it under a pressure of 3 MPa for 2 minutes to press it into a ceramic green body with a diameter of 12 mm and a height of 5 mm.

[0213] (8) Sintering: The ceramic green body is placed in a high-temperature furnace and heated to 800℃ at a heating rate of 3℃ / min, held for 4 hours to remove the binder. After removing the binder, the temperature is increased to 1415℃ at a heating rate of 4℃ / min and held for 4 hours. Finally, the temperature is reduced to 800℃ at a cooling rate of 3℃ / min and allowed to cool naturally to obtain the microwave dielectric ceramic material Mg. 1.8 (Ni 0.5 Co 0.5 ) 0.2 Al 3.9 (Ge 0.5 Mg 0.5 ) 0.1 Si5O 18 ;

[0214] (9) Sample mechanical treatment and performance testing: The sintered microwave dielectric ceramic sample is ground and polished with a polishing machine, then ultrasonically cleaned, dried, and then its performance tested and packaged.

[0215] The microwave dielectric ceramic material prepared in this embodiment has a dielectric constant of 4.51, a quality factor of 132016 GHz, and a resonant frequency temperature coefficient of -21.34 ppm / ℃.

[0216] Example 14

[0217] This embodiment provides a low dielectric constant, low loss microwave dielectric ceramic material Mg 1.8 (Ni 0.75 Co 0.25 ) 0.2 Al 3.85 (Ge 0.5 Mg 0.5 ) 0.15 Si5O 18 The preparation method includes the following steps:

[0218] (1) Weighing and batching: Weigh and batch the MgO, NiO, CoO, Al2O3, GeO2 and SiO2 raw materials that have undergone calcination and drying pretreatment according to the chemical formula stoichiometric ratio.

[0219] (2) First ball milling: Transfer the ingredients into the ball mill jar, add a certain amount of anhydrous ethanol as liquid medium and zirconium dioxide as grinding medium, seal the ball mill jar and place it in the ball mill for 12 hours. The speed is set to 220 r / min. After ball milling, put the slurry into the tray and transfer it into the oven to dry to constant weight.

[0220] (3) Pre-calcination: After drying, the powder is ground through a 100-mesh nylon sieve and then transferred into an alumina crucible. It is then placed in a high-temperature furnace and heated to 1200℃ at a heating rate of 3℃ / min and held for 4 hours.

[0221] (4) Secondary ball milling: Pour the pre-calcined raw material back into the ball mill jar, add a certain amount of anhydrous ethanol as a liquid medium, and put it into the ball mill for 12 hours. The speed is set to 220 r / min.

[0222] (5) Drying: Pour the slurry after the second ball milling into a tray and transfer it into an oven to dry until constant weight.

[0223] (6) Granulation: Grind the dried block raw material into powder, add binder (10wt% polyvinyl alcohol solution), mix evenly, pass through a 100-mesh nylon sieve, and select the powder that passes through as the raw material for the next step.

[0224] (7) Green body pressing: Weigh about 1 gram of powder and pour it into the mold. Then place it in the press and hold it under a pressure of 3 MPa for 2 minutes to press it into a ceramic green body with a diameter of 12 mm and a height of 5 mm.

[0225] (8) Sintering: The ceramic green body is placed in a high-temperature furnace and heated to 800℃ at a heating rate of 3℃ / min, held for 4 hours to remove the binder. After removing the binder, the temperature is increased to 1405℃ at a heating rate of 4℃ / min and held for 4 hours. Finally, the temperature is reduced to 800℃ at a cooling rate of 3℃ / min and allowed to cool naturally to obtain the microwave dielectric ceramic material Mg. 1.8 (Ni 0.75 Co 0.25 ) 0.2 Al 3.85 (Ge 0.5 Mg 0.5 ) 0.15 Si5O 18 ;

[0226] (9) Sample mechanical treatment and performance testing: The sintered microwave dielectric ceramic sample is ground and polished with a polishing machine, then ultrasonically cleaned, dried, and then its performance tested and packaged.

[0227] The microwave dielectric ceramic material prepared in this embodiment has a dielectric constant of 4.59, a quality factor of 153386 GHz, and a resonant frequency temperature coefficient of -25.518 ppm / ℃.

[0228] Example 15

[0229] This embodiment provides a low dielectric constant, low loss microwave dielectric ceramic material Mg 1.8 (Ni 0.5 Co 0.5 ) 0.2 Al 3.8 (Ge 0.5 Mg 0.5 ) 0.2Si5O 18 The preparation method includes the following steps:

[0230] (1) Weighing and batching: Weigh and batch the MgO, NiO, CoO, Al2O3, GeO2 and SiO2 raw materials that have undergone calcination and drying pretreatment according to the chemical formula stoichiometric ratio.

[0231] (2) First ball milling: Transfer the ingredients into the ball mill jar, add a certain amount of anhydrous ethanol as liquid medium and zirconium dioxide as grinding medium, seal the ball mill jar and place it in the ball mill for 12 hours. The speed is set to 220 r / min. After ball milling, put the slurry into the tray and transfer it into the oven to dry to constant weight.

[0232] (3) Pre-calcination: After drying, the powder is ground through a 100-mesh nylon sieve and then transferred into an alumina crucible. It is then placed in a high-temperature furnace and heated to 1200℃ at a heating rate of 3℃ / min and held for 4 hours.

[0233] (4) Secondary ball milling: Pour the pre-calcined raw material back into the ball mill jar, add a certain amount of anhydrous ethanol as a liquid medium, and put it into the ball mill for 12 hours. The speed is set to 220 r / min.

[0234] (5) Drying: Pour the slurry after the second ball milling into a tray and transfer it into an oven to dry until constant weight.

[0235] (6) Granulation: Grind the dried block raw material into powder, add binder (10wt% polyvinyl alcohol solution), mix evenly, pass through a 100-mesh nylon sieve, and select the powder that passes through as the raw material for the next step.

[0236] (7) Green body pressing: Weigh about 1 gram of powder and pour it into the mold. Then place it in the press and hold it under a pressure of 3 MPa for 2 minutes to press it into a ceramic green body with a diameter of 12 mm and a height of 5 mm.

[0237] (8) Sintering: The ceramic green body is placed in a high-temperature furnace and heated to 800℃ at a heating rate of 3℃ / min, held for 4 hours to remove the binder. After removing the binder, the temperature is increased to 1410℃ at a heating rate of 4℃ / min and held for 4 hours. Finally, the temperature is reduced to 800℃ at a cooling rate of 3℃ / min and allowed to cool naturally to obtain the microwave dielectric ceramic material Mg. 1.8 (Ni 0.5 Co 0.5 ) 0.2 Al 3.8 (Ge 0.5 Mg 0.5 ) 0.2 Si5O 18 ;

[0238] (9) Sample mechanical treatment and performance testing: The sintered microwave dielectric ceramic sample is ground and polished with a polishing machine, then ultrasonically cleaned, dried, and then its performance tested and packaged.

[0239] The microwave dielectric ceramic material prepared in this embodiment has a dielectric constant of 4.71, a quality factor of 97818 GHz, and a resonant frequency temperature coefficient of -22.89 ppm / ℃.

[0240] Example 16

[0241] This embodiment provides a low dielectric constant, low loss microwave dielectric ceramic material Mg 1.8 (Ni 0.75 Co 0.25 ) 0.2 Al 3.75 (Ge 0.5 Mg 0.5 ) 0.25 Si5O 18 The preparation method includes the following steps:

[0242] (1) Weighing and batching: Weigh and batch the MgO, NiO, CoO, Al2O3, GeO2 and SiO2 raw materials that have undergone calcination and drying pretreatment according to the chemical formula stoichiometric ratio.

[0243] (2) First ball milling: Transfer the ingredients into the ball mill jar, add a certain amount of anhydrous ethanol as liquid medium and zirconium dioxide as grinding medium, seal the ball mill jar and place it in the ball mill for 12 hours. The speed is set to 220 r / min. After ball milling, put the slurry into the tray and transfer it into the oven to dry to constant weight.

[0244] (3) Pre-calcination: After drying, the powder is ground through a 100-mesh nylon sieve and then transferred into an alumina crucible. It is then placed in a high-temperature furnace and heated to 1200℃ at a heating rate of 3℃ / min and held for 4 hours.

[0245] (4) Secondary ball milling: Pour the pre-calcined raw material back into the ball mill jar, add a certain amount of anhydrous ethanol as a liquid medium, and put it into the ball mill for 12 hours. The speed is set to 220 r / min.

[0246] (5) Drying: Pour the slurry after the second ball milling into a tray and transfer it into an oven to dry until constant weight.

[0247] (6) Granulation: Grind the dried block raw material into powder, add binder (10wt% polyvinyl alcohol solution), mix evenly, pass through a 100-mesh nylon sieve, and select the powder that passes through as the raw material for the next step.

[0248] (7) Green body pressing: Weigh about 1 gram of powder and pour it into the mold. Then place it in the press and hold it under a pressure of 3 MPa for 2 minutes to press it into a ceramic green body with a diameter of 12 mm and a height of 5 mm.

[0249] (8) Sintering: The ceramic green body is placed in a high-temperature furnace and heated to 800℃ at a heating rate of 3℃ / min, held for 4 hours to remove the binder. After removing the binder, the temperature is increased to 1410℃ at a heating rate of 4℃ / min and held for 4 hours. Finally, the temperature is reduced to 800℃ at a cooling rate of 3℃ / min and allowed to cool naturally to obtain the microwave dielectric ceramic material Mg. 1.8 (Ni 0.75 Co 0.25 ) 0.2 Al 3.75 (Ge 0.5 Mg 0.5 ) 0.25 Si5O 18 ;

[0250] (9) Sample mechanical treatment and performance testing: The sintered microwave dielectric ceramic sample is ground and polished with a polishing machine, then ultrasonically cleaned, dried, and then its performance tested and packaged.

[0251] The microwave dielectric ceramic material prepared in this embodiment has a dielectric constant of 4.67, a quality factor of 93450 GHz, and a resonant frequency temperature coefficient of -22.04 ppm / ℃.

[0252] Comparative Example 1

[0253] This comparative example provides a method for preparing the microwave dielectric ceramic material Mg2Al4Si5O4:

[0254] (1) Weighing and batching: Weigh and batch the MgO, Al2O3 and SiO2 raw materials that have undergone calcination and drying pretreatment according to the chemical formula stoichiometric ratio.

[0255] (2) First ball milling: Transfer the ingredients into the ball mill jar, add a certain amount of anhydrous ethanol as liquid medium and zirconium dioxide as grinding medium, seal the ball mill jar and place it in the ball mill for 12 hours. The speed is set to 220 r / min. After ball milling, put the slurry into the tray and transfer it into the oven to dry to constant weight.

[0256] (3) Pre-calcination: After drying, the powder is ground through a 100-mesh nylon sieve and then transferred into an alumina crucible. It is then placed in a high-temperature furnace and heated to 1200℃ at a heating rate of 3℃ / min and held for 4 hours.

[0257] (4) Secondary ball milling: Pour the pre-calcined raw material back into the ball mill jar, add a certain amount of anhydrous ethanol as a liquid medium, and put it into the ball mill for 12 hours. The speed is set to 220 r / min.

[0258] (5) Drying: Pour the slurry after the second ball milling into a tray and transfer it into an oven to dry until constant weight.

[0259] (6) Granulation: Grind the dried block raw material into powder, add binder (10wt% polyvinyl alcohol solution), mix evenly, pass through a 100-mesh nylon sieve, and select the powder that passes through as the raw material for the next step.

[0260] (7) Green body pressing: Weigh about 1 gram of powder and pour it into the mold. Then place it in the press and hold it under a pressure of 3 MPa for 2 minutes to press it into a ceramic green body with a diameter of 12 mm and a height of 5 mm.

[0261] (8) Sintering: The ceramic green body is placed in a high-temperature furnace and heated to 800°C at a heating rate of 3°C / min and held for 4 hours to remove the binder. After removing the binder, the temperature is raised to 1430°C at a heating rate of 4°C / min and held for 4 hours. Finally, the temperature is lowered to 800°C at a cooling rate of 3°C / min and then cooled naturally to obtain the microwave dielectric ceramic material Mg2Al4Si5O4.

[0262] (9) Sample mechanical treatment and performance testing: The sintered microwave dielectric ceramic sample is ground and polished with a polishing machine, then ultrasonically cleaned, dried, and then its performance tested and packaged.

[0263] The microwave dielectric ceramic material prepared in this comparative example has a dielectric constant of 4.36, a quality factor of 42170 GHz, and a resonant frequency temperature coefficient of -33 ppm / ℃.

[0264] Comparative Example 2

[0265] This comparative example provides a microwave dielectric ceramic material Mg 1.8 Ni 0.1 Co 0.1 Preparation method of Al4Si5O4:

[0266] (1) Weighing and batching: Weigh and batch the MgO, Al2O3, SiO2, NiO and CoO raw materials that have undergone calcination and drying pretreatment according to the chemical formula stoichiometric ratio.

[0267] (2) First ball milling: Transfer the ingredients into the ball mill jar, add a certain amount of anhydrous ethanol as liquid medium and zirconium dioxide as grinding medium, seal the ball mill jar and place it in the ball mill for 12 hours. The speed is set to 240 r / min. After ball milling, put the slurry into the tray and transfer it into the oven to dry to constant weight.

[0268] (3) Pre-calcination: After drying, the powder is ground through a 100-mesh nylon sieve and then transferred into an alumina crucible. It is then placed in a high-temperature furnace and heated to 1200℃ at a heating rate of 4℃ / min and held for 4 hours.

[0269] (4) Secondary ball milling: Pour the pre-calcined raw material back into the ball mill jar, add a certain amount of anhydrous ethanol as a liquid medium, and put it into the ball mill for 12 hours. The speed is set to 240 r / min.

[0270] (5) Drying: Pour the slurry after the second ball milling into a tray and transfer it into an oven to dry until constant weight.

[0271] (6) Granulation: Grind the dried block raw material into powder, add binder (8 wt% polyvinyl alcohol solution), mix evenly, pass through a 100-mesh nylon sieve, and select the powder that passes through as the raw material for the next step.

[0272] (7) Green body pressing: Weigh about 1 gram of powder and pour it into the mold. Then place it in the press and hold it under a pressure of 3 MPa for 2 minutes to press it into a ceramic green body with a diameter of 12 mm and a height of 5 mm.

[0273] (8) Sintering: The ceramic green body is placed in a high-temperature furnace and heated to 800℃ at a heating rate of 4℃ / min, held for 4 hours to remove the binder. After removing the binder, the temperature is increased to 1420℃ at a heating rate of 4℃ / min and held for 4 hours. Finally, the temperature is reduced to 800℃ at a cooling rate of 4℃ / min and allowed to cool naturally to obtain the microwave dielectric ceramic material Mg. 1.8 Ni 0.1 Co 0.1 Al4Si5O4;

[0274] (9) Sample mechanical treatment and performance testing: The sintered microwave dielectric ceramic sample is ground and polished with a polishing machine, then ultrasonically cleaned, dried, and then its performance tested and packaged.

[0275] The microwave dielectric ceramic material prepared in this comparative example has a dielectric constant of 4.4, a quality factor of 66539 GHz, and a resonant frequency temperature coefficient of -21.54 ppm / ℃.

[0276] Comparative Example 3

[0277] This comparative example provides a low dielectric constant, low loss microwave dielectric ceramic material Mg2Al. 3.7 (Mn 0.5 Zn 0.5 ) 0.3 Si5O 18 The preparation method includes the following steps:

[0278] (1) Weighing and batching: Weigh and batch the raw materials MgO, NiO, CoO, Al2O3, MnO2, ZnO and SiO2 that have undergone calcination and drying pretreatment according to the chemical formula stoichiometric ratio.

[0279] (2) First ball milling: Transfer the ingredients into the ball mill jar, add a certain amount of anhydrous ethanol as liquid medium and zirconium dioxide as grinding medium, seal the ball mill jar and place it in the ball mill for 12 hours. The speed is set to 220 r / min. After ball milling, put the slurry into the tray and transfer it into the oven to dry to constant weight.

[0280] (3) Pre-calcination: After drying, the powder is ground through a 100-mesh nylon sieve and then transferred into an alumina crucible. It is then placed in a high-temperature furnace and heated to 1200℃ at a heating rate of 3℃ / min and held for 4 hours.

[0281] (4) Secondary ball milling: Pour the pre-calcined raw material back into the ball mill jar, add a certain amount of anhydrous ethanol as a liquid medium, and put it into the ball mill for 12 hours. The speed is set to 220 r / min.

[0282] (5) Drying: Pour the slurry after the second ball milling into a tray and transfer it into an oven to dry until constant weight.

[0283] (6) Granulation: Grind the dried block raw material into powder, add binder (10wt% polyvinyl alcohol solution), mix evenly, pass through a 100-mesh nylon sieve, and select the powder that passes through as the raw material for the next step.

[0284] (7) Green body pressing: Weigh about 1 gram of powder and pour it into the mold. Then place it in the press and hold it under a pressure of 3 MPa for 2 minutes to press it into a ceramic green body with a diameter of 12 mm and a height of 5 mm.

[0285] (8) Sintering: The ceramic green body is placed in a high-temperature furnace and heated to 800℃ at a heating rate of 3℃ / min, held for 4 hours to remove the binder. After removing the binder, the temperature is increased to 1275℃ at a heating rate of 4℃ / min and held for 4 hours. Finally, the temperature is reduced to 800℃ at a cooling rate of 3℃ / min and allowed to cool naturally to obtain the microwave dielectric ceramic material Mg2Al. 3.85 (Mn 0.5 Zn 0.5 ) 0.15 Si5O 18 ;

[0286] (9) Sample mechanical treatment and performance testing: The sintered microwave dielectric ceramic sample is ground and polished with a polishing machine, then ultrasonically cleaned, dried, and then its performance tested and packaged.

[0287] The microwave dielectric ceramic material prepared in this comparative example has a dielectric constant of 4.53, a quality factor of 150500GHz, and a resonant frequency temperature coefficient of -32ppm / ℃.

[0288] Figure 1 For Mg in Comparative Examples 1-3 and Examples 1-4 1.8 (Ni 1-x Co x ) 0.2 Al 4-y (Mn 0.5 Zn 0.5 ) y Si5O 18 The microwave dielectric properties are shown in the curves of Al doping concentration γ. It can be seen that the dielectric constant does not change significantly, ranging from 4.36 to 4.88. In Example 2, when the Al doping concentration γ is 0.15, Q×f reaches its maximum value of 86058 GHz, and τ... f The optimal value is -19.2 ppm / ℃; the temperature coefficient of the resonant frequency ranges from -28.69 to -19.2 ppm / ℃.

[0289] Figure 2 For Mg in Comparative Examples 1-2 and Examples 5-8 1.8 (Ni 1-x Co x ) 0.2 Al 4-y (Mn 0.5 Mg 0.5 ) y Si5O 18 The microwave dielectric properties are shown in the curves of Al site doping concentration γ; it can be seen that the dielectric constant remains almost constant, ranging from 4.36 to 4.77; in Example 6, Q×f reaches a maximum value of 125691 GHz; obviously, using Mn 4+ -Mg 2+ The substitution of Al sites with composite ions improves the Q×f value. When 0.1≤y≤0.25, low-loss cordierite-type microwave dielectric ceramics are obtained.

[0290] Figure 3 For Mg in Comparative Examples 1-2 and Examples 9-12 1.8 (Ni 1-x Co x ) 0.2 Al 4-y (Ge 0.5 Zn 0.5 ) y Si5O 18The microwave dielectric properties are shown in the curves of Al site doping concentration γ. It can be seen that the dielectric constant fluctuates within a certain range, but the change is very small, ranging from 4.36 to 4.80. In Example 10, the Q×f value reaches a maximum of 119721 GHz. Clearly, using Ge... 4+ -Zn 2+ Replacing the Al sites improves the Q×f value. When 0.1≤y≤0.2, low-loss cordierite-type microwave dielectric ceramics are obtained.

[0291] Figure 4 For Mg in Comparative Examples 1-2 and Examples 13-16 1.8 (Ni 1-x Co x ) 0.2 Al 4-y (Ge 0.5 Mg 0.5 ) y Si5O 18 The microwave dielectric properties are shown in the curves of Al site doping concentration γ. It can be seen that the dielectric constant changes very little, ranging from 4.36 to 4.71. In Example 14, the Q×f value reaches a maximum of 153386 GHz. Clearly, replacing Al sites with Ge4+-Mg2+ composite ions improves the Q×f value. When 0.1 ≤ γ ≤ 0.25, a low-loss cordierite-type microwave dielectric ceramic is obtained.

[0292] Table 1 shows the orthogonal experimental table designed in this invention; it is a three-factor, four-level orthogonal table, where Ni 1-x Co x Since x has only three levels, the fourth level was filled with 0.50 using the pseudo-level method.

[0293] The embodiments described above are merely examples illustrating several implementations of the present invention, and their descriptions are quite specific and detailed. They should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the scope of protection of the present invention. Therefore, the scope of protection of this patent should be determined by the appended claims.

Claims

1. A K4 low-dielectric-low-loss cordierite-type microwave dielectric ceramic, characterized in that, Its chemical formula is Mg 1.8 (Ni 1- x Co x ) 0.2 Al 4-y (A 0.5 B 0.5 ) y Si5O 18 Where the range of the subscript x is 0.25 ≤ x ≤ 0.75; the range of the subscript y is 0.10 ≤ y ≤ 0.25; A 0.5 B 0.5 Represents Mn 0.5 Zn 0.5 Mn 0.5 Mg 0.5 、Ge 0.5 Zn 0.5 、Ge 0.5 Mg 0.5 Any one of them; Ni 2+ -Co 2+ The substitution of some Mg in the magnesia cordierite lattice 2+ Lattice position; Mn 4+ -Mg 2+ 、Ge 4+ -Mg 2+ Mn 4+ -Zn 2+ 、Ge 4+ -Zn 2+ Any group of composite ions in the magnesia cordierite lattice replaces a portion of the Al in the magnesia cordierite lattice. 3+ Lattice positions to achieve composite ion doping of Al 3+ ; When Mn 4+ -Zn 2+ Composite ion-doped Al 3+ At that time, the quality factor of the low-dielectric-low-loss cordierite microwave dielectric ceramic is 24400GHz~86100GHz, the temperature coefficient of the resonant frequency is -28.70~-19.10ppm / ℃, and the dielectric constant is 4.40~4.90; When Mn 4+ -Mg 2+ Composite ion-doped Al 3+ At that time, the quality factor of the low-dielectric-low-loss cordierite microwave dielectric ceramic is 102900GHz~125700GHz, the temperature coefficient of the resonant frequency is -25.90~-21.20ppm / ℃, and the dielectric constant is 4.60~4.

80. When Ge 4+ -Zn 2+ Composite ion-doped Al 3+ At that time, the quality factor of the low-dielectric-low-loss cordierite microwave dielectric ceramic is 31000GHz~119700GHz, the temperature coefficient of the resonant frequency is -22.57~-17.67ppm / ℃, and the dielectric constant is 4.39~4.

80. When Ge 4+ -Mg 2+ Composite ion-doped Al 3+ At that time, the quality factor of the low-dielectric-low-loss cordierite microwave dielectric ceramic is 935000GHz~153400GHz, the temperature coefficient of the resonant frequency is -25.50~-21.30ppm / ℃, and the dielectric constant is 4.50~4.

70.

2. The preparation method of K4 low-dielectric-low-loss cordierite-type microwave dielectric ceramic as described in claim 1, characterized in that, Includes the following steps: (1) Using MgO, NiO, CoO, Al2O 3、 MnO2, SiO2 and ZnO are used as raw materials, dispersed in a reaction medium according to the stoichiometric ratio of chemical formulas, and then ground and dried to obtain powder. The chemical formula is: Mg 1.8 (Ni 1-x Co x ) 0.2 Al 4-y (Mn 0.5 Zn 0.5 ) y Si5O 18 Where the range of the subscript x is 0.25≤x≤0.75; and the range of the subscript y is 0.10≤y≤0.25; (2) The powder is pre-calcined, then ground twice, dried, and granulated to obtain Ni-doped material. 2+ Co 2+ Mn 4+ Zn 2+ Ceramic raw materials; The pre-firing process conditions are as follows: heating to 1200℃ at a heating rate of 3℃ / min and holding for 4 hours, and finally cooling down to 800℃ at a cooling rate of 3℃ / min and then naturally cooling. (3) Sintering the doped Ni 2+ Co 2+ Mn 4+ Zn 2+ The microwave dielectric ceramic material is obtained from the ceramic raw materials. The sintering process conditions are as follows: the ceramic green body is placed in a high-temperature furnace and heated to 800°C at a heating rate of 3°C / min, and held at that temperature for 4 hours to remove the binder; after removing the binder, the temperature is raised to 1300°C to 1360°C at a heating rate of 4°C / min and held at that temperature for 4 hours; finally, the temperature is lowered to 800°C at a cooling rate of 3°C / min and then allowed to cool naturally. Before sintering, the following steps are also included: doping Ni 2+ Co 2+ Mn 4+ Zn 2+ The ceramic raw materials are ground evenly, and a 10wt% polyvinyl alcohol solution is added. After mixing evenly, the mixture is passed through a 100-mesh nylon sieve. Each time, about 1 gram of powder is weighed and poured into a steel mold for pressing. The powder is pressed into a cylinder with a pressure of 1-5 MPa and held for 2 minutes.

3. The preparation method of K4 low-dielectric-low-loss cordierite-type microwave dielectric ceramic as described in claim 1, characterized in that, Includes the following steps: (1) Using MgO, NiO, CoO, Al2O 3、 MnO2 and SiO2 are used as raw materials, dispersed in a reaction medium according to the stoichiometric ratio of the chemical formula, and then ground and dried in one step to obtain powder. The chemical formula is: Mg 1.8 (Ni 1-x Co x ) 0.2 Al 4-y (Mn 0.5 Mg 0.5 ) y Si5O 18 Where the range of the subscript x is 0.25≤x≤0.75; and the range of the subscript y is 0.10≤y≤0.25; (2) The powder is pre-calcined, then ground twice, dried, and granulated to obtain Ni-doped material. 2+ Co 2+ Mn 4+ Mg 2+ The ceramic raw materials; the pre-firing process conditions are: heating to 1200℃ at a heating rate of 3℃ / min and holding for 4 hours, and finally cooling to 800℃ at a cooling rate of 3℃ / min and then naturally cooling. (3) Sintering the doped Ni 2+ Co 2+ Mn 4+ Mg 2+ The microwave dielectric ceramic material is obtained from the ceramic raw materials. The sintering process conditions are as follows: the ceramic green body is placed in a high-temperature furnace and heated to 800°C at a heating rate of 3°C / min, and held at that temperature for 4 hours to remove the binder; after removing the binder, the temperature is raised to 1395°C to 1420°C at a heating rate of 4°C / min and held at that temperature for 4 hours; finally, the temperature is lowered to 800°C at a cooling rate of 3°C / min and then allowed to cool naturally. Before sintering, the following steps are also included: doping Ni 2+ Co 2+ Mn 4+ Mg 2+ The ceramic raw materials are ground evenly, and a 10wt% polyvinyl alcohol solution is added. After mixing evenly, the mixture is passed through a 100-mesh nylon sieve. Each time, about 1 gram of powder is weighed and poured into a steel mold for pressing. The powder is pressed into a cylinder with a pressure of 1-5 MPa and held for 2 minutes.

4. The preparation method of K4 low-dielectric-low-loss cordierite-type microwave dielectric ceramic as described in claim 1, characterized in that, Includes the following steps: (1) Using MgO, NiO, CoO, Al2O 3、 GeO2, SiO2 and ZnO are used as raw materials, dispersed in a reaction medium according to the stoichiometric ratio of the chemical formula, and then ground and dried in one step to obtain powder. The chemical formula is: Mg 1.8 (Ni 1-x Co x ) 0.2 Al 4-y (Ge 0.5 Zn 0.5 ) y Si5O 18 Where the range of the subscript x is 0.25≤x≤0.75; and the range of the subscript y is 0.10≤y≤0.25; (2) The powder is pre-calcined, then ground twice, dried, and granulated to obtain Ni-doped material. 2+ Co 2+ Ge 4+ Zn 2+ The ceramic raw materials; the pre-firing process conditions are: heating to 1200℃ at a heating rate of 3℃ / min and holding for 4 hours, and finally cooling to 800℃ at a cooling rate of 3℃ / min and then naturally cooling. (3) Sintering the doped Ni 2+ Co 2+ Ge 4+ Zn 2+ The microwave dielectric ceramic material is obtained from the ceramic raw materials. The sintering process conditions are as follows: The ceramic green body is placed in a high-temperature furnace and heated to 800°C at a heating rate of 3°C / min, held at this temperature for 4 hours to remove the binder; after removing the binder, the temperature is increased to 1340°C–1420°C at a heating rate of 4°C / min and held for 4 hours, finally cooled to 800°C at a cooling rate of 3°C / min and allowed to cool naturally. Before sintering, the following steps are also included: Ni-doped... 2+ Co 2+ Ge 4+ Zn 2+ The ceramic raw materials are ground evenly, and a 10wt% polyvinyl alcohol solution is added. After mixing evenly, the mixture is passed through a 100-mesh nylon sieve. Each time, about 1 gram of powder is weighed and poured into a steel mold for pressing. The powder is pressed into a cylinder with a pressure of 1-5 MPa and held for 2 minutes.

5. The preparation method of K4 low-dielectric-low-loss cordierite-type microwave dielectric ceramic as described in claim 1, characterized in that, Includes the following steps: (1) Using MgO, NiO, CoO, Al2O3, GeO2 and SiO2 as raw materials, disperse them in the reaction medium according to the stoichiometric ratio of the chemical formula, grind them once, and dry them to obtain powder; The chemical formula is: Mg 1.8 (Ni 1-x Co x ) 0.2 Al 4-y (Ge 0.5 Mg 0.5 ) y Si5O 18 Where the range of the subscript x is 0.25≤x≤0.75; and the range of the subscript y is 0.10≤y≤0.25; (2) The powder is pre-calcined, then ground twice, dried, and granulated to obtain Ni-doped material. 2+ Co 2+ Ge 4+ Mg 2+ The ceramic raw materials; the pre-firing process conditions are: heating to 1200℃ at a heating rate of 3℃ / min and holding for 4 hours, and finally cooling to 800℃ at a cooling rate of 3℃ / min and then naturally cooling. (3) Sintering the doped Ni 2+ Co 2+ Ge 4+ Mg 2+ The microwave dielectric ceramic material is obtained from the ceramic raw materials. The sintering process conditions are as follows: The ceramic green body is placed in a high-temperature furnace and heated to 800°C at a heating rate of 3°C / min, held at this temperature for 4 hours to remove the binder; after removing the binder, the temperature is increased to 1395°C–1420°C at a heating rate of 4°C / min and held for 4 hours, finally cooled to 800°C at a cooling rate of 3°C / min and allowed to cool naturally. Before sintering, the following steps are also included: Ni-doped... 2+ Co 2+ Ge 4+ Mg 2+ The ceramic raw materials are ground evenly, and a 10wt% polyvinyl alcohol solution is added. After mixing evenly, the mixture is passed through a 100-mesh nylon sieve. Each time, about 1 gram of powder is weighed and poured into a steel mold for pressing. The powder is pressed into a cylinder with a pressure of 1-5 MPa and held for 2 minutes.

6. The preparation method of K4 low-dielectric-low-loss cordierite-type microwave dielectric ceramic as described in claim 5, characterized in that, In step (1), the chemical formula is: Mg 1.8 (Ni 0.75 Co 0.25 ) 0.2 Al 3.85 (Ge 0.5 Mg 0.5 ) 0.15 Si5O 18 ; In step (3), the dielectric constant of the obtained microwave dielectric ceramic material is 4.59, the quality factor is 153386GHz, and the temperature coefficient of the resonant frequency is -25.518ppm / ℃.

Citation Information

Patent Citations

  • A microwave dielectric ceramic material, a composite material, its preparation method, and its applications.

    CN115141006B